Nursing Care in Patients with COVID-19: A Proposed Algorithm - Kartal Erdost, Şerife; Demiröz, Anıl; Arı, Arzu; Karadede, Özkan; Kartoğlu Gürler, Sevdan; Yalçın, Can Ege; Çınar, Fatih; Gemicioğlu, Bilun; Çetinkale, Oğuz (Cerrahpaşa Medical Journal, 2023)
Objective: Since coronavirus disease 2019 affected the whole world in such a short time, it has many unknown aspects. These unknown, scary, and deadly aspects have put people, including healthcare workers, in panic. The objective of the study is to create a new care and treatment algorithm to facilitate and manage the nursing care practices in line with the physiological and psychosocial needs of patients diagnosed with coronavirus disease 2019. Methods: This study was carried out by filtering from the information obtained from 135 patients whose follow-up and care were the responsibility of the authors. The findings and demographic information essential to the study were collected by the authors. Results: The approaches developed and applied by the authors were handled analytically, and algorithms were created for patients diagnosed with coronavirus disease 2019. Conclusion: The proposed algorithms can serve as a guide for clinics and nurses who are new to the field or have no experience in taking care of these patients. Cite this article as: Kartal Erdost Ş, Demiröz A, Arı A, et al. Nursing care in patients with COVID-19: A proposed algorithm. Cerrahpaşa Med J. 2023;47(1):100-104.